USALI adapted to the small independent hotels - Correia, Henrique (2021)
A set of management accounting techniques has been used by hoteliers in order to aptimize decision making processes by hotel managers, as it is crucial for success on a global scale. Prior studies related to the characterization of management accounting in the lodging industry in several countries have recognized the Uniform System of Accounts on Lodging Industry (USALI) as one of the management accounting techniques. USALI is a powerful management accounting technique in the means that allows the standardization and comparability of information. Nevertheless, USALI has had a higher degree of utilization in the hotel chains given that it is used to support the information processing. It is known that in many countries, including Portugal, corporate structure is composed by micro and small enterprises. Thus the aim of this paper was to understand the contribution of the USALI in the small independent hotels, through of a USALI adjusted. The first step of this study was to analyse the Portuguese case by conducting a survey to obtain data, which has been submitted to a statistical analysis. It was concluded in relation to operating departments, the most frequently used are: "Rooms" and "Food & Beverage" (F&B). It will be necessary to reduce a lot of items and schedules to adapt the USALI for small independent hotels.